IMPLEMENTASI PENGEMBANGAN SDM PADA KINERJA KARYAWAN PENJUALAN PT AKUSARA KABUPATEN GROBOGAN - Agid Viki Pradipta, Aditya (Study of Applied Entrepreneurship, 2024)
Human resource development is the most important factor for a company that is used to increase employee performance productivity and expand employee capacity. This research aims to analyze and find out the implementation of human resource development on the performance of sales employees at PT Akusara. Research methods use qualitative methods by conducting interviews with objects to obtain the necessary information and data. The results of this research show that the Human Resource Development that has been implemented at Akusara PT is by performing 3 techniques namely Needs Analysis, Program Design and Evaluation. The research results to refer to the perspective of the research object are sales employees with a working time of less than 1 year and sales workers with working time over 1 year. Where both explain that with the development of human resources this can develop the ability of sales employees in particular in achieving the sales targets set by the company.